AutoKeras for Fake News Identification in Arabic: Leveraging Deep Learning with an Extensive Dataset - Matti, Raed; Yousif, Suhad (Al-Nahrain Journal of Science, 2023)
Social media and the World Wide Web have led to a worrying rise in spreading false information, which presents a significant worldwide issue. Identifying and preventing false information is crucial in promoting an informed and knowledgeable society. The identification of false information, specifically in the Arabic dialect, presents inherent difficulties due to its diverse characteristics and linguistic intricacies. This study implements AutoKeras, a deep learning-based machine learning framework. Using advanced optimization techniques, the neural network architecture search, hyperparameter adjustments, and model selection can all be automated in AutoKeras. Therefore, it is suitable for our fake news detection task. The methodology employs proficient deep learning algorithms and natural language processing methods to acquire distinct characteristics that enable accurate differentiation between genuine and fake news. The present study uses various sources, including news websites, social media platforms, and blogs, to construct the dataset. The AutoKeras-based approach is superior to multiple state-of-the-art approaches to detecting fabricated news in Arabic, as evidenced by the experimental results. The suggested method outperforms 93.2% accuracy in identifying fake news, demonstrating its superior efficacy. This demonstrates the great promise of the deep learning-based Auto model for detecting false information.